Effectiveness of spatial mitigation for the George River Caribou Herd within the military training area of Labrador and Québec - Trimper, Perry G.; Chubbs, Tony E. (Rangifer, 2003)
The George River Caribou (Rangifer tarandus) Herd (GRCH) regularly migrates through the military Low Level Training Area (LLTA) used for jet training out of 5 Wing Goose Bay, Labrador. Potential disturbance to caribou by military aircraft has been mitigated through the reconfiguration of the LLTA in 1996 away from the traditional migration routes and the establishment of closure areas based on the locations of >20 adults fitted with satellite telemetry collars. In 2000 and 2001, we conducted seven aerial surveys to examine the caribou distribution and abundance within the northern portion and adjacent area of the LLTA during post-calving, summer dispersal, pre-rut and late winter. We flew transects to examine approximately 10% of areas traditionally used during each period. The timing and direction of cari¬bou movements through this region were similar to that observed in the 1990s. Collared caribou were a good indicator of movements of the GRCH through the LLTA. Closure areas based on the location of satellite collars and direction of movement, were found to enclose the majority of caribou observed within the LLTA. Most GRCH activity now occurs outside the LLTA as a result of reconfiguration.